Prospective, Randomized, Sham‐Control, Double Blind, Crossover Trial of Subthreshold Spinal Cord Stimulation at Various Kilohertz Frequencies in Subjects Suffering From Failed Back Surgery Syndrome (SCS Frequency Study). Issue 5 (2nd April 2018) - Al‐Kaisy, Adnan; Palmisani, Stefano; Pang, David; Sanderson, Karen; Wesley, Samuel; Tan, Ye; McCammon, Sheryl; Trescott, Andrea
Abstract : Introduction: The increasing use of high frequency paresthesia‐free spinal cord stimulation has been associated with improved outcomes in the therapy of neuropathic pain. What is unknown is the effect of varying frequency on pain relief and the placebo effect. Materials and Methods: This is a prospective, randomized, sham‐controlled double blind crossover study. Subjects with predominantly axial low back pain undergoing spinal cord stimulation therapy for failed back surgery syndrome were randomized to sham, 1200 Hz, 3030 Hz, and 5882 Hz with a four‐phase crossover design over 12 weeks. Results: Twenty‐four patients were randomized in the study. The mean low back pain score at baseline was 7.75. The mean low back pain scores on a 10 cm visual analog scale during the randomized crossover phase were 4.83, 4.51, 4.57, and 3.22, for sham, 1200 Hz, 3030 Hz, and 5882 Hz, respectively, with the lowest low back pain score observed in the 5882 Hz frequency group ( p  = 0.002). Of note, sham stimulation resulted in a reduction of pain by −2.92 cm and was not significantly different from stimulation at 1200 Hz and 3030 Hz. Conclusions: This randomized crossover study demonstrated that 5882 Hz stimulation can produce significant pain relief for axial low back pain compared with lower frequencies and sham stimulation. Sham stimulation produced similar analgesic effects to 1200 Hz and 3030 Hz and this effect may influence future neuromodulation clinical trial designs.